A Stochastic Model of Wealth Accumulation with Class Division. (31st May 2013) - Russo, Alberto
Abstract This paper is aimed at contributing to the literature on income and wealth inequality by proposing a simple stochastic model in which wealth accumulation depends on the 'social relation' between two classes: capitalists or workers. As a result, the society may evolve towards an unequal outcome with few rich and many poor individuals. We study the dynamic properties of the model by means of computer simulations. A maximum likelihood estimation procedure is applied to analyse the Pareto or power law tail of wealth distribution. We also provide a scenario analysis to explore the system's behaviour under alternative parameter settings.